Investigating the Effect of Project-Based Learning on the Science Learning Outcomes of Fifth Grade Students in Elementary School - Zahra, Putri; Rahmiati, Rahmiati (FKIP - Universitas Riau, 2025)
This study aims to examine the impact of implementing the Project-Based Learning (PjBL) model on the academic achievement of fifth-grade students in the subject of Science and Social Studies (IPAS) at SDN Meruya Utara 08 Pagi. The research employed a quasi-experimental design involving two groups: an experimental group taught using the PjBL approach and a control group that received conventional instruction. Data were collected through multiple-choice tests that had undergone content validation and reliability testing. The analysis revealed that the average score of students in the experimental group was 85.74, while the control group obtained an average of 71.00. Statistical analysis using an Independent Sample t-Test yielded a significance value of 0.000 (p < 0.05), indicating a meaningful difference between the two groups. Furthermore, the effect size analysis using Cohen’s d produced a value of 2.142, which falls into the category of a large effect. These findings demonstrate that the application of the PjBL model has a positive and substantial influence on students’ IPAS learning outcomes, offering an effective alternative strategy for enhancing student engagement and deepening conceptual understanding.